An ultracapacitor-based no-break system for microcomputers - Gouvea, Evaldo Chagas [UNESP]; Marcelino, Marcio Abud [UNESP]; Grandinetti, Francisco José [UNESP]; Prado, Pedro Paulo Leite do (Springer, 2014)
This work aims at presenting a no-break system for microcomputers using ultracapacitors in replacement of the conventional chemical batteries. We analyzed the most relevant data about average power consumption of microcomputers, electrical and mechanical characteristics of ultracapacitors and operation of no-break power circuits, to propose a configuration capable of working properly with a microcomputer switching mode power supply. Our solution was a sixteen-component ultracapacitor bank, with a total capacitance of 350 F and voltage of 10.8 V, adequate to integrate a low-capacity no-break system, capable of feeding a load of 180 Wh, during 75 s. Our proposed no-break increases the reliability of microcomputers by reducing the probability of user data losses, in case of a power grid failure, offering, so, a high benefit-cost ratio. The replacement of the battery by ultracapacitors allows a quick no-break recharge and low maintenance costs, since these modern components have a lifetime longer than the batteries. Moreover, this solution reduces the environmental impact and eliminates the constant recharge of the energy storage device.
Keywords: Energy; No-break; Uninterruptible power supply; Ultracapacitor